2005
DOI: 10.1007/s00425-005-0097-8
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and subsequent interaction with 14-3-3 proteins regulate plastid glutamine synthetase in Medicago truncatula

Abstract: In this report we demonstrate that plastid glutamine synthetase of Medicago truncatula (MtGS2) is regulated by phosphorylation and 14-3-3 interaction. To investigate regulatory aspects of GS2 phosphorylation, we have produced non-phosphorylated GS2 proteins by expressing the plant cDNA in E. coli and performed in vitro phosphorylation assays. The recombinant isoenzyme was phosphorylated by calcium dependent kinase(s) present in leaves, roots and nodules. Using an (His)6-tagged 14-3-3 protein column affinity pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 44 publications
2
39
0
Order By: Relevance
“…Another potential level of complexity in the nod26-GS interaction comes from the observation that both binding partners are subject to post-translational phosphorylation (5,(55)(56)(57). In the case of nod26, the unique site of phosphorylation is Ser 262 (55), which resides in the C-terminal domain, which is the site of GS interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential level of complexity in the nod26-GS interaction comes from the observation that both binding partners are subject to post-translational phosphorylation (5,(55)(56)(57). In the case of nod26, the unique site of phosphorylation is Ser 262 (55), which resides in the C-terminal domain, which is the site of GS interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary analyses suggest that nod26 peptides that are phosphorylated at Ser 262 retain the ability to bind to GS in vitro, but the influence of phosphorylation on the assembly and activity of the complex in vivo remains to be addressed. Cytosolic GS 1 is also a target for posttranslational phosphorylation by various protein kinases in plant tissues (56,57), with phosphorylation potentially leading to interaction with 14-3-3 proteins (56) and other unidentified phosphoproteins (57). The interplay between phosphorylation, GS regulation, and interaction with nod26 and other potential regulatory targets and the effects of these on N 2 fixation and assimilation in response to environmental cues remain a topic for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…3D). Post-translational regulation by a 14-3-3 protein has previously been reported to play a positive role in GS activation (Finnemann and Schjoerring, 2000;Lima et al, 2006).…”
Section: Responses Of Gs Protein and Activity To High Ammonium Levelsmentioning
confidence: 99%
“…Changes in MDA content were observed in the tomato seedlings treated with different concentrations of Pb +2 , indicating that the samples were under stress. It has been demonstrated that increased lipid peroxidation is a characteristic feature of oxidative stress caused by unbalanced equilibrium between ROS production and scavenging or defense mechanisms under heavy metal stress (Smirnoff 1993;Mittler 2002;Lima et al 2006).…”
Section: +2mentioning
confidence: 99%